SIMULATION IMAGE GENERATOR, SIMULATION IMAGE GENERATION METHOD, COMPUTATION PROGRAM, AND RECORDING MEDIUM RECORDED WITH PROGRAM - OGURO HISASHI (2006)
PROBLEM TO BE SOLVED: To allow an interactive viewing of high real time property, without causing a speed reduction in use, even when using a large capacity of highly definition three-dimensional data to reproduce an object with high quality. SOLUTION: This simulation image generator has an image data generated based on the three-dimensional data expressing an object surface within a three-dimensional scene, and based on camera information expressing a view point operation for photographing the object within the three-dimensional scene, and for indicating information as to the object surface in a corresponding point on the object surface corresponding to a position of each picture element in every of the picture elements, a function for inputting the camera information, a function for inputting a simulation condition, and a function for finding a picture element value when the object is brought into the simulation condition within the three-dimensional scene, in the every picture element, based on the image data and the camera information, and for displaying it. COPYRIGHT: (C)2007,JPO&INPIT